AkvaGIS: An open source tool for water quantity and quality management. (June 2019) - Criollo, Rotman; Velasco, Violeta; Nardi, Albert; Manuel de Vries, Luis; Riera, Celia; Scheiber, Laura; Jurado, Anna; Brouyère, Serge; Pujades, Estanislao; Rossetto, Rudy; Vázquez-Suñé, Enric
Abstract: AkvaGIS is a novel, free and open source module included in the FREEWAT plugin for QGIS that supplies a standardized and easy-to-use workflow for the storage, management, visualization and analysis of hydrochemical and hydrogeological data. The main application is devised to simplify the characterization of groundwater bodies for the purpose of building rigorous and data-based environmental conceptual models (as required in Europe by the Water Framework Directive). For data-based groundwater management, AkvaGIS can be used to prepare input files for most groundwater flow numerical models in all of the available formats in QGIS. AkvaGIS is applied in the Walloon Region (Belgium) to demonstrate its functionalities. The results support a better understanding of the hydrochemical relationship among aquifers in the region and can be used as a baseline for the development of new analyses, e.g., further delineation of nitrate vulnerable zones and management of the monitoring network to control chemical spatial and temporal evolution. AkvaGIS can be expanded and adapted for further environmental applications as the FREEWAT community grows. Highlights: AkvaGIS is a novel and open source module included in the FREEWAT plugin for QGIS. AkvaGIS main application is to simplify the characterization of groundwater bodies. AkvaGIS purpose is to build rigorous and data-based environmental conceptual models. AkvaGIS is applied in the Walloon Region (Belgium) to demonstrate its capabilities. AkvaGIS is freely available for its application and/or for its further development.